AS level and A level : economics [ economics : teacher's resource - Grant; Bamford (New York: Cambridge University Press, 2011)
CD-ROM for Windows XP/Vista and MAC OSK 10.3.9 or higher.
FAS
COP
Keywords: Economics; Economics -- -- Problems, exercises, etc